Wind-induced fatigue analysis of high-rise guyed lattice steel towers. (February 2022) - Ribeiro, D.; Bragança, C.; Montenegro, P.A.; Carvalho, H.; Costa, B.; Marques, F.
Abstract: Wind-induced fatigue is a major issue for the design of slender high-rise structures. However, there are still few studies focused on this topic, resulting in a lack of practical design procedures for this type of structures. This paper aims to fill this gap by presenting a complete and practical methodology for the wind-induced fatigue life assessment of high-rise towers and its application to a 120 m cable-stayed steel tower composed by a modular lattice. The wind actions were considered as the sum of the quasi-static component according to international codes and a numerically generated, trough an ergodic stochastic process, turbulent component which is based on the Kaimal wind spectrum. Real wind measurements were also taken for a period of 15 months on a nearby MET station which, when compared with the normative scenario, proved to be much less conservative and were not used for the safety analysis. The wind velocities were used as inputs for a nonlinear dynamic analysis from which stress time histories were derived for 10 potentially critical structural details. The damage in each detail was computed through the application of the Rainflow counting algorithm and Palmgren-Miner's damage accumulation law, indicating the connection region between the modules as the critical detail with respect to fatigue damage.